ANALISIS ALIH KODE DAN CAMPUR KODE DALAM DIALOG MAHASISWA DAN MAHASISWI MANGGARAI PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MAHASARASWATI DENPASAR - Ni Made Sueni (Wacana Saraswati Majalah Ilmiah Tentang Bahasa Sastra Dan Pembelajarannya, 2021)
The process of communication and social interaction raises the tendency of a speaker to utilize the potential for language variations. One variation of the language is code switching and code mixing to maintain togetherness in the community. Code switching and code mixing are changes in the use of a particular language or variety of languages to other languages. This study aims to describe certain forms of code switching and interfering forms found in the Student and Student Dialogue in Indonesian Language and Literature Education Study Program Faculty of Teacher Training and Education (FKIP) Mahasaraswati University (Unmas) Denpasar. The results of the study show that there is indeed code switching and code mixing in the Manggarai student and student dialogue. took place at the Indonesian Language and Literature Education Program (PSP) Teacher Training and Education Faculty (FKIP) Mahasaraswati University Denpasar (Unmas). The forms of code switching and code mixing in the dialogues of Manggarai students and students are in the form of sentences and words. The factors that influence code switching and code mixing in the dialogues of Manggarai students and students take place, namely. Speakers or speakers, listeners or opponents of speech, habitual factors, changing situations, the presence of third people, changing situations from formal to informal, changing topic of conversation, forgetting local language, affirmation or to clarify, to trends and not to be outdated. Key words: Code Switching and Code Mixing, Students of Flores Manggarai Students